The short-term effect of contact lens wear on blink characteristics. Issue 5 (October 2022) - Navascues-Cornago, Maria; Sun, Tiejing; Read, Michael L.; Morgan, Philip B.
Abstract: Purpose: The aim of this pilot study was to investigate the initial effect of contact lens wear on spontaneous blink characteristics. Methods: This was a randomised, crossover pilot study. Spontaneous blinking was recorded using a high-speed infrared camera in ten subjects with three different soft contact lenses (spherical hydrogel, spherical silicone hydrogel and toric hydrogel), one rigid contact lens and without contact lenses. Custom semi-automated software was used to determine palpebral aperture height, interblink interval (IBI), blink speed, blink completeness and blink duration. Results: The IBI was significantly greater for non-lens wear compared with the silicone hydrogel [ratio (95% CI): 1.34 (1.16, 1.55), p < 0.0001], toric hydrogel [1.28 (1.10, 1.48), p = 0.0001] and rigid corneal lenses [1.48 (1.27, 1.73), p < 0.0001]. The spherical silicone hydrogel lens showed greater closing-phase speed than non-lens wear [mean difference (95% CI): 27.4 (5.6, 49.1) mm/s, p = 0.006]. Shorter total blink duration was found for non-lens wear compared with any of the lens types [spherical hydrogel: ratio 0.89 (0.81, 0.98), p = 0.01; spherical silicone hydrogel: 0.87 (0.80, 0.95), p = 0.0001; toric hydrogel: 0.90 (0.83, 0.98), p = 0.004; and rigid corneal: 0.88 (0.82, 0.96), p = 0.0004]. Opening-phase speed (p = 0.12) and blink completeness metrics (all p > 0.5) were not influenced by wearing condition. Conclusion: This work showed that short-term contact lens wear influenced the palpebral aperture height, IBI, speed and duration of the blink, and the effect is dependent on the contact lens type. The completeness of the blink was not altered by contact lens wear. Future work should be conducted to assess the effect of long-term wear of different contact lens types on blink characteristics. The measurement of spontaneous blinking characteristics represents an immediate, sensitive and non-invasive evaluation of the impact of a contact lens on the ocular surface.